2016
DOI: 10.3892/etm.2016.2986
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein D, a clinical biomarker for chronic obstructive pulmonary disease with excellent discriminant values

Abstract: Biological markers can help to better identify a disease or refine its diagnosis. In the present study, the association between surfactant protein D (SP-D) and chronic obstructive pulmonary disease (COPD) was studied among subjects consulting for respiratory diseases or symptoms and was compared with C-reactive protein (CRP) and fibrinogen. A further aim of this study was to identify the optimal cut-off point of SP-D able to discriminate COPD patients. A case-control study including 90 COPD patients, 124 asthm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…Akiki et al measured serum SP-D, CRP, and fibrinogen levels in patients with COPD. In their study, SP-D levels were found significantly and positively associated with COPD, whereas serum CRP and plasma fibrinogen levels were not [32].…”
Section: Discussionmentioning
confidence: 78%
“…Akiki et al measured serum SP-D, CRP, and fibrinogen levels in patients with COPD. In their study, SP-D levels were found significantly and positively associated with COPD, whereas serum CRP and plasma fibrinogen levels were not [32].…”
Section: Discussionmentioning
confidence: 78%
“…In COPD, serum SP‐D was found to be associated with the BODE index of severity and to mortality . However, serum SP‐D levels were not found to be associated with COPD disease severity in the ECLIPSE study as well as in other additional smaller studies …”
Section: Introductionmentioning
confidence: 79%
“…During the period from June 2011 to April 2013, 90 COPD and 123 asthmatic patients were recruited from the outpatient clinics of the Pulmonology Department of the Saint George Hospital University Medical Center, Beirut, Lebanon. In addition, a total of 223 controls were recruited from the general population . All participants were 18 years old or above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SP-D is positively asso ciated with the severity of COPD, and SP-D may successfully differentiate COPD from other respiratory symptoms or diseases (36). Serum SP-D levels are remarkably increased in acute exacerbations of patients with COPD, and are negatively correlated with the lung function in COPD patients (37).…”
Section: Discussionmentioning
confidence: 97%